Clinical Diagnostic Accuracy of Onychomycosis: A Multispecialty Comparison Study. (3rd July 2018) - Li, David G.; Cohen, Jeffrey M.; Mikailov, Anar; Williams, Ramone F.; Laga, Alvaro C.; Mostaghimi, Arash
Abstract : Although onychomycosis can be diagnosed clinically, many guidelines still recommend pathologic confirmation of the diagnosis prior to initiation of systemic treatment. We retrospectively reviewed results from 541 toenail clippings (160 by dermatologists, 198 by podiatrists, and 183 by other provider types) sent to the Brigham and Women's Department of Dermatopathology between January 2000 and December 2013 for confirmatory periodic acid-Schiff (PAS) testing of clinically diagnosed onychomycosis. Of these, 93 (58.1%), 125 (63.1%), and 71 (38.8%) were sent for confirmation of onychomycosis (as opposed to diagnosis of onychodystrophy) by dermatologists, podiatrists, and other provider types, respectively. Confirmatory PAS stains were positive in 70 (75.3%), 101 (80.8%), and 47 (66.2%) of samples ordered by dermatologists, podiatrists, and other providers, respectively. Our study demonstrates that clinical diagnosis of onychomycosis in the appropriate clinical setting is accurate across specialties. Further prospective investigation on the accuracy of clinical diagnosis of onychomycosis may be beneficial.